Effective Mall Management - The Critical Success Factor for Malls Today - Zameer, Asif (Indian Journal of Marketing, 2006)
The mall-mania seems to have truly gripped the country. To the present generation shopping means much more than a mere necessity and malls are now fast becoming image benchmarks for communities. Everyone seems to have been taken in by the euphoria about the potential of Organized Retailing sector - be it retailers, mall-developers or consumers. The fast growing middle-class population and the rise in women workforce and consumerism over the decade are the major force in driving demand. Daily we have news, reports & discussions in all kinds of media about organized retail sector, shopping center development, FDI in retail and so on and so forth. Mall-management is a term, which figures repeatedly in most of these, but generally it is not understood properly. Traditionally in India, mall-management has been equated to facilities management. As we shall see, its scope of activities is much beyond facilities management, which is essentially a maintenance job.